Sistem Numerasi Mesir Kuno - Siagian, Philips Pasca G; Sitorus, Januari Partogi; Nasution, Rahmi Radita; Angraini, Ririn Tri; Br Rambe, Rukiyah; Siagian, Nuraifah (JURNAL PENELITIAN PENDIDIKAN MIPA, 2024)
This research discusses the history of the development of numbers in Ancient Egypt and examines its implications for mathematics learning. Through literature studies and analysis of mathematical artifacts from Ancient Egypt, this research explains how the Ancient Egyptian number system was developed, how the system was used in everyday life, and how the history of mathematics can be used to increase student motivation and understanding. Apart from that, this research also evaluates the extent to which prospective teachers understand the history of the development of numbers in Ancient Egypt. It is hoped that the results of this research can contribute to the development of a more relevant and interesting mathematics curriculum. This research uses qualitative methods with data collection techniques using library research. Library research is a technique of collecting information and data from various sources such as documents, books, magazines and historical records. Literature study involves the use of book references or previous research results which are used as a theoretical basis for analyzing research problems